The Earliest Known 'Sign of Tanit' Revealed in 11th Century BCE Building at Megiddo. (2nd January 2017) - Arie, Eran
Abstract : During the 2008 excavation season at Megiddo, a small copper alloy object was uncovered in a clean, early Iron I context. It is the earliest sign of Tanit known to date. The article surveys the roots of this Phoenician symbol from the Iron Age to the Hellenistic period in the Phoenician homeland, and evaluates the new find's significance in terms of its date and regional origin.